Qualitative and Quantitative Assessment of Vascular Changes in Diabetic Macular Edema after Dexamethasone Implant Using Optical Coherence Tomography Angiography - Toto, Lisa; D’Aloisio, Rossella; Di Nicola, Marta; Di Martino, Giuseppe; Di Staso, Silvio; Ciancaglini, Marco; Tognetto, Daniele; Mastropasqua, Leonardo (International journal of molecular sciences, 2017)
The aim of this study was to investigate retinal and choriocapillaris vessel changes in diabetic macular edema (DME) after the intravitreal dexamethasone implant (IDI) using optical coherence tomography angiography (OCTA). Moreover, a comparison between morphological and functional parameters of DME and healthy patients was performed. Twenty-five eyes of 25 type 2 diabetic retinopathy patients complicated by macular edema (DME group) and 25 healthy subjects (control group) were enrolled. Superficial capillary plexus density (SCPD) and deep capillary plexus density (DCPD) in the foveal and parafoveal areas, choricapillary density (CCD) and optic disc vessel density (ODVD) were detected using OCTA at baseline and after 7, 30, 60, 90 and 120 days post injection. Best corrected visual acuity (BCVA), retinal sensitivity, and central retinal thickness (CMT) were also evaluated in both groups of patients. A statistically significant difference between the two groups (DME and controls) was found in terms of functional (MP, p < 0.001 and BCVA, p < 0.001) and morphological (CMT, p < 0.001; SCPD in the parafoveal area, p < 0.001; DCPD in the foveal area, p < 0.05 and parafoveal area, p < 0.001; CCD, p < 0.001) parameters. After the treatment, SCPD and DCPD in the foveal and parafoveal areas did not modify significantly during the follow up.